MODEL OF MULTIPLE-CRITERIA DECISION-MAKING (MCDM) IN SELECTION OF RICE SEEDS WITH TOPSIS METHOD - Nono Heryana; Rudi Aprianto; Rini Mayasari (LPPM STMIK Pringsewu, 2020)
The use of rice seeds is very influential in the productivity of agricultural businesses, one of the problems is in determining the rice seeds to be planted, rice seeds are the primary input in the success of rice farming. This study tries to apply the Multiple Criteria Decision Making (MCDM) to the selection of rice seeds using the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) approach. In developing the system, this study uses the System Development Life Cycle (SDLC) method with 4 (four) phases of system development, namely PADI (Planning, Analysis, Design and Implementation), the TOPSIS Method are the method used to determine the best alternative decision making, based on the criteria set is the shape of rice, types of rice, grain and colour of the seeds. The results of this work can facilitate farmers in choosing rice seeds to be planted.